RBP7 knockdown inhibits proliferation of human hepatocellular carcinoma and activates the p38 MAPK pathway - Li, Jinhai; Zhai, Huawei; Cai, Fujing; Zhang, Xian; Zhou, Yu; Li, Shuqun; Song, Huachun; Zhang, Haifeng; Sun, Guangzheng; Zhu, Minghui; Yuan, Jing; Zhang, Ningxin; et al. (Frontiers in Oncology, 2025)
BackgroundRetinoid metabolism is critical for maintaining liver homeostasis, and its dysregulation is closely associated with liver diseases. Retinol binding protein 7 (RBP7) involves in retinoids transport, particularly in liver, indicating its importance in hepatic functions. However, its specific role in hepatocellular carcinoma (HCC) tumorigenesis remains unclear and needs to further investigation.MethodsBioinformatics was employed to assess RBP7 expression across different cohorts. The expression level of RBP7 in cells were further validated using qRT-PCR and western blot. Additionally, we investigated the impact of RBP7 knockdown on cell cycle-related genes, apoptosis-related proteins, and p38 MAPK signaling activity. Functional assays, including CCK8, colony formation, flow cytometry (FACS) analysis, Annexin V/7-AAD staining and xenograft tumor assay, were performed to determine the vitro and in vivo role of RBP7. Survival analysis was conducted to evaluate the correlation between RBP7 expression and the prognosis of HCC patients.ResultsRBP7 is frequently elevated in HCC tumor tissues, particularly in early-stage patients. Notably, high RBP7 expression is closely correlated with overall survival (OS) and disease-specific survival (DSS) in HCC patients. Knockdown of RBP7 inhibited cell proliferation in vitro and suppressed tumor growth in vivo by inducing cell cycle arrest and apoptosis. Mechanistically, we found that RBP7 knockdown-induced suppression of HCC cell proliferation was associated with increased phosphorylation of p38 MAPK.ConclusionOur findings demonstrate that RBP7 suppression activates p38 MAPK signaling pathway, leading to impaired cell proliferation. These results suggest that RBP7 may serve as both a prognostic biomarker and a promising therapeutic target for HCC.